Virtual Reality Reality As A Method Of Shooting Basketball Practice: A Systematic Study Of Its Effectiveness And Implementation In The Sport Of Basketball - Agus Sutriawan; Hikmad Hakim; Muh Nugrah Setyawan (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Virtual Reality (VR) technology has grown rapidly and is increasingly applied in sports training, including basketball. This study aims to systematically review the effectiveness of virtual reality as a basketball shooting training method. The method used is a systematic literature review (SLR) following PRISMA guidelines. Searches were conducted through Google Scholar, PubMed, Scopus, and SINTA databases with a publication range of 2014–2024. Of 348 articles identified, 28 articles met the inclusion criteria and were analyzed through narrative synthesis. Risk of bias assessment using JBI Critical Appraisal Tools showed that 64.3% of studies had high performance bias due to difficulties in blinding, a common limitation in VR training research. The findings indicate that VR-based basketball shooting training is effective in improving shooting accuracy (average improvement of 24.1% vs. 11.8% conventional), spatial perception, and athlete confidence. VR allows athletes to practice in a safe, repetitive, and measurable simulation environment through mechanisms of augmented real-time feedback, immersive mental rehearsal, and programmed variability of practice. However, limitations include high implementation costs (USD 3,000–50,000), cybersickness risks (50% of studies), and lack of real haptic feedback. The novelty of this review lies in its simultaneous analysis of neuromotor mechanisms and contextual implementation challenges in developing countries. This review recommends integrating VR as a supplement (30–40% of training time) to conventional training to maximize overall basketball shooting training effectiveness